Testing GeoGebra as an effective tool to improve the understanding of the concept of limit on engineering students (2019)
The impact GeoGebra on the teaching of the concept of limit was analyzed. Two groups of engineering students, studying differential calculus, served as control and test groups. The traditional teaching, based on examples solved by hand, was given to the control group while a series of activities involving the usage of the mathematical software GeoGebra were applied in an attempt of improving the degree of assimilation on the concept of limits.